The Influence of Using the Animated Film Media Boboiboy Galaksi Gentar on Fantasy Story Writing Skill - Isnaini Aminatuz Zahra; Trinil Dwi Turistiani (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Digital transformation in the world of education has encouraged changes in learning strategies, including the use of audiovisual media in the form of animated films as a more engaging and interactive learning tool. This research is motivated by the importance of learning innovation to improve students' attention, motivation, and writing skills. The purpose of this study was to determine the effect of using the animated film Boboiboy Galaksi Gentar on participants' fantasy story writing skills. This study used a quantitative descriptive method. The study took place in the odd semester of the 2025/2026 academic year at SMPN 19 Surabaya. The study used a quantitative approach with an experimental method based on a true experimental design. The study population was grade VII students who took the pre-test, took part in fantasy story writing skills learning, and took the post-test. They numbered 29 students in grade VI-A as the treatment group and 22 students in grade VII-J as the control group. The sample was determined to be 26 students in the treatment group and 20 students in the control group. Data collection techniques were carried out through observation, pre-test, and post-test to measure the improvement in students' writing skills before and after the treatment was given. The results showed that the average pretest score in the experimental class was 65.75, increasing to 83.75 in the posttest. Meanwhile, the control class experienced an increase from 68.30 to 79.38. The increase in the experimental class was higher than the control class with a difference of 18 points. Based on these results, it can be concluded that the use of the animated film Boboiboy Galaksi Gentar has a significant effect on improving the fantasy narrative writing ability of seventh grade students at SMPN 19 Surabaya.